2015
DOI: 10.14295/bds.2015.v18i1.1076
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malocclusion and orthodontic treatment needs among down syndrome sudanese individuals

Abstract: <p><strong>Objective<em>:</em></strong> To determine the prevalence of malocclusion and orthodontic treatment needs in Sudanese’s Down syndrome individuals in Khartoum area. <strong>Material and Methods: </strong>A total of 75 (37 males and 38 females) Down syndrome individuals age ranging from 6-28 years of age, were clinically examined after obtaining their guardian’s consent. Malocclusion was determined based on Angle and Incisor classification of malocclusion. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…37 However, this result is low compared with a study done in Kenya (72%) (29), Rwanda (93%), 38 Iran (87%), 39 Colombia (88%), global burden of malocclusion in Africa (89%) 20 and Sudan (85.3%). 40 Besides, lower results were reported in Brazil (20.0%) 41 and Bangladesh (24.7%). 21 The difference between our study and others might be due to the ethnicity difference and the use of variable criteria for the classification of the malocclusion.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…37 However, this result is low compared with a study done in Kenya (72%) (29), Rwanda (93%), 38 Iran (87%), 39 Colombia (88%), global burden of malocclusion in Africa (89%) 20 and Sudan (85.3%). 40 Besides, lower results were reported in Brazil (20.0%) 41 and Bangladesh (24.7%). 21 The difference between our study and others might be due to the ethnicity difference and the use of variable criteria for the classification of the malocclusion.…”
Section: Discussionmentioning
confidence: 90%
“…20 Meanwhile, a systematic review done in Iran showed only 5.5% of the patients in Iran had a class-III relation. 39 However, a study done in Sudan found 58.7% 40 of the study participants had class-III malocclusion. This difference might be the study done in Sudan includes Down syndrome patients who are more prone to jaw development problems.…”
Section: Dovepressmentioning
confidence: 95%
“…Among the 390 children, in this study, 65% presented malocclusion; the result is in agreement with previous studies, which report prevalence rates ranging from 60 to 70%. Angle class I was the most prevalent, followed by classes II and III, which is also in agreement with the previous studies 24,25 ., conducted in different countries, which report a high prevalence of malocclusion 26,27 , that impact the functional, emotional and social aspects of children´s life 16,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with deformities may be physically, socially, or mentally challenged and comprise more marked oral healthrelated problems, either because of their authentic disability or because of associated medical conditions . 4 Malocclusion is irregularity which leads to disfigurement hampering the function of teeth, and this disfigurement or imperfection is likely to be an impediment to the patient's physical or emotional comfort. 5 Malocclusion compromises the health of oral cavity and also can lead to social problems to affected patients.…”
Section: Introductionmentioning
confidence: 99%